ANALISIS PENALARAN ADAPTIF SISWA DALAM MENYELESAIKAN SOAL LITERASI MATEMATIKA TERINTEGRASI ISLAM DITINJAU DARI GAYA KOGNITIF - Ud'hiyata Zahbi; Wahyu Henky Irawan (Universitas Bhinneka PGRI, 2024)
This research was conducted to determine students' adaptive reasoning in solving Islamic integrated mathematical literacy questions based on cognitive style. This research uses an exploratory qualitative approach with a phenomenological nature. The subjects of this research consisted of 6 students from class VIII Islamic Junior High School Al-Faqih Nganjuk which consists of 3 field dependent type students and 3 field independent type students. Data collection was carried out by administering adaptive reasoning tests and interviews. The data obtained was transcribed and then analyzed based on the adaptive reasoning indicators of Killpatrick et al.'s theory. which consists of making conjectures, giving reasons for a statement, drawing conclusions from a statement, checking the validity of an argument, and finding patterns in mathematical phenomena. Based on data analysis from 6 subjects with different cognitive styles, differences were found in their adaptive reasoning. Students with a field dependent cognitive style do not meet the adaptive reasoning indicators in solving Islamic integrated mathematical literacy questions. They are only able to fulfill 3-4 indicators out of 5 indicators of adaptive reasoning. Meanwhile, students with a field independent cognitive style fulfill the adaptive reasoning indicators in solving Islamic integrated mathematics literacy problems.